2013
DOI: 10.1016/j.phrp.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Heavy Rain and Typhoon on Allergic Disease

Abstract: ObjectivesAllergic disease may be increased by climate change. Recent reports have shown that typhoon and heavy rain increase allergic disease locally by concentration of airborne allergens of pollen, ozone, and fungus, which are causes of allergic disease. The objective of this study was to determine whether typhoon and heavy rain increase allergic disease in Korea.MethodsThis study included allergic disease patients of the area declared as a special disaster zone due to storms and heavy rains from 2003 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(17 reference statements)
0
13
1
Order By: Relevance
“…Previous studies provide conflicting evidence on whether asthma exacerbation events or acute respiratory illnesses increase during flooding [28,69,70]. In the present study, we found a marginal increase in asthma-related ED visits during the first postflood period only in the highly flooded tracts (RR = 1.08).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Previous studies provide conflicting evidence on whether asthma exacerbation events or acute respiratory illnesses increase during flooding [28,69,70]. In the present study, we found a marginal increase in asthma-related ED visits during the first postflood period only in the highly flooded tracts (RR = 1.08).…”
Section: Discussioncontrasting
confidence: 70%
“…the 16 cites during 2007 [70]. Reacher et al [28] showed a threefold increase in worsening of asthma among adults in flooded areas, however, the study cautioned about interpreting the association as they found a trend of declining risk for increasing depth of flooding.…”
Section: Discussionmentioning
confidence: 95%
“…The available information on changes in respiratory illness was contradictory. During the first week after a typhoon, a review of insurance claims from typhoon-affected areas found a small increase in patients seeking care for allergic rhinitis (rate ratio: 1.19; 95% CI, 1.15-1.23) but a decrease in patients seeking care for asthma (rate ratio: 0.90; 95% CI, 0.86-0.93); 112 an island-wide treatment facility study found no significant increase in visits for asthma or chronic obstructive pulmonary disease in the week after a cyclone, 87 although other treatment facilities saw significant increases in visits for asthma two weeks 67 and one month post-hurricane 79 . In the one to three months after a hurricane, children with chronic conditions were more likely to have worsened asthma (16.3% versus 1.9%; P<.01) than children without chronic conditions 113 .…”
Section: Resultsmentioning
confidence: 99%
“…We found few papers linking floods to asthma. Only three of the four papers reviewed supported the linkage, while the fourth paper found a negative association (Park et al 2013). Of the supporting papers, one found that response was partially mediated by psychological distress, and that asthma negatively correlated to flooding depth, which contradicts their findings (Reacher et al 2004).…”
Section: Discussionmentioning
confidence: 97%